(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the integration of the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach into the educational process, its role in developing students’ thinking, and its impact on the formation of critical thinking and independent problem-solving skills. The article presents the results of incorporating the STEAM approach into the educational process, practical approaches, and methodological proposals based on modern experiences.